Tumor-derived extracellular vesicles mediate cell-specific uptake and facilitate enhanced doxorubicin delivery in breast cancer - Alagundagi, Dhananjay B.; Thomas, Mahima Rachel; Sangamesh, Vinay C.; J Rajendra, Vinay Kumar; Shetty, Vijith V.; Kabekkodu, Shama Prasada; Shetty, Praveenkumar; Patil, Prakash (Frontiers in Pharmacology, 2026)
BackgroundChemotherapy suppresses tumor growth and metastasis, but its efficacy is limited by non-specificity, systemic toxicity, poor accumulation and side effects. Extracellular vesicles (EVs) derived from cells have recently been tested for carrying drugs due to their biocompatibility, stability, and ability to cross biological barriers. We aimed to investigate the potential of drug incorporation to breast cancer (BC) cells-derived EVs and their targeted cell-specific delivery.MethodsEVs were isolated from MDA-MB-231 and MCF7 cells and characterized by nanoparticle tracking analysis and scanning electron microscopy. The cellular uptake of EVs assessed by PKH67 labelling and fluorescent microscopy. Doxorubicin (dox) was incorporated into EVs by sonication, entrapment was confirmed by high-performance liquid chromatography (HPLC). Further, BC cells cytotoxicity, apoptosis, and wound healing was determined for therapeutic efficacy of dox-loaded EVs compared to free dox.ResultsEVs had average size of 126.6 ± 58.6 nm (MDA-MB-231) and 163.3 ± 25.7 nm (MCF7), with spherical morphology. EVs exhibited significantly higher autologous uptake compared to allogenic, heterologous or non-cancerous uptake, confirming parent cell-type specificity. Dox entrapment was 22.84% and 29.87%. Furthermore, dox-EVs reduced parent cell viability to 46.1% (MDA-MB-231) and 35.3% (MCF7) compared to free dox treatment (63.4% and 62.1%). Additionally, dox-EVs suppressed wound healing and enhanced apoptosis more effectively than free Dox, while EVs alone promoted cell proliferation.ConclusionOverall, EVs uptake is cell-specific, and drug incorporation enhanced targeted cell cytotoxicity, highlighting their potential as personalized carriers for precision chemotherapy. However, validation of these results through mechanistic and in vivo studies are warranted to extrapolate for therapeutic potential.